Changes in the prevalence of polycystic ovary syndrome in China over the past decade - Yang, Rui; Li, Qin; Zhou, Zehong; Qian, Weiping; Zhang, Jian; Wu, Ze; Jin, Lei; Wu, Xueqing; Zhang, Cuilian; Zheng, Beihong; Tan, Jichun; Hao, Guimin; et al. (The Lancet regional health. Western Pacific, 2022)
Polycystic ovary syndrome (PCOS) has become a major international public health concern. However, because of controversy about the diagnostic criteria and patient selection, estimates of its absolute prevalence and change with time vary greatly. We conducted two consecutive nationwide epidemiological surveys of the prevalence of PCOS in representative samples of reproductive-aged women in China in 2010 and 2020. Face-to-face interviews were performed by trained interviewers in each survey. All participants completed a questionnaire and underwent a physical examination, blood sampling, and transvaginal pelvic ultrasound. We assessed hyperandrogenism (H), chronic anovulation (O), and polycystic ovaries (P) to classify the presence of PCOS using the Rotterdam criteria. The prevalence of PCOS among reproductive-aged women was estimated after consideration of differential probabilities of selection and population distribution. We conducted a logistic regression analysis by using the probability of PCOS as a function of the survey year to acquire the trend information across the years. 28,739 respondents completed the survey, including 15,924 in the previously published 2010 survey and 12,815 in the new 2020 survey. In 2020, 826 participants could be diagnosed as having PCOS, with a weighted prevalence of 7.8% (95%CI: 7.0%, 9.0%) among women aged 20-49 years, leading to an estimate of 24.0 million women of reproductive age affected by this condition in China as a whole. The estimated prevalence in 2020 was higher than that of a decade ago despite identical research methods suggesting a two-thirds increase over the study period. Women with PCOS in 2020 also appeared to have a more severe phenotype overall than those of a decade ago, possibly reflecting a significantly higher prevalence of obesity, hyperandrogenism, and infertility. The prevalence of PCOS in Chinese women has increased significantly over the past 10 years. PCOS is a significant public health problem in women of reproductive age in China and national policy and guidelines should be re-examined in the light of the current data. National Key R&D Program of China and the National Natural Science Foundation of China.